2022
DOI: 10.3928/00989134-20220908-04
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Stress Reduction Program for Family Caregivers of Persons With Advanced Dementia: A Pilot Study

Abstract: The current study sought to pilot test and examine the effects of an integrative stress reduction program (ISRP) on caregiver stress and sleep quality and behavioral and psychological symptoms of dementia (BPSD) of care recipients. Family caregivers ( N = 12) of persons with moderate to severe dementia were recruited from memory clinics in Thailand. Twelve caregivers participated in five educational sessions on dementia care, stress, and BPSD management over 4 weeks. The Relative Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The program offers a new option for training Thai caregivers of people with dementia to improve their health and caregiving skills that can be implemented in community settings, where few such options exist. 18…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The program offers a new option for training Thai caregivers of people with dementia to improve their health and caregiving skills that can be implemented in community settings, where few such options exist. 18…”
Section: Discussionmentioning
confidence: 99%
“…Third, the length of the program of 4 weeks was not burdensome for the caregivers in this study nor in the pilot study. 18 Those who participated in the intervention completed the entire program, except for 2 caregivers who experienced the death of their family member, indicating a high motivation to learn about caregiving and address their stress. Overall, our results are consistent with studies of Kor et al 13 and Shata et al 12 who also reported large effects of their interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations